2018
DOI: 10.1371/journal.pone.0193212
|View full text |Cite
|
Sign up to set email alerts
|

An efficient and reliable DNA-based sex identification method for archaeological Pacific salmonid (Oncorhynchus spp.) remains

Abstract: Pacific salmonid (Oncorhynchus spp.) remains are routinely recovered from archaeological sites in northwestern North America but typically lack sexually dimorphic features, precluding the sex identification of these remains through morphological approaches. Consequently, little is known about the deep history of the sex-selective salmonid fishing strategies practiced by some of the region’s Indigenous peoples. Here, we present a DNA-based method for the sex identification of archaeological Pacific salmonid rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…While zooarchaeological analyses are also well-suited to reconstructing catch size profiles, particularly when larger quantities of fish head bones are preserved, there are many cases where this will not be possible using traditional osteological analyses, such as when most fish bones recovered archaeologically are from vertebrae. In these cases, particularly when combined with aDNA techniques (Royle et al, 2018), isotopic analyses of archaeological fish have significant potential to reveal ancient fisheries management practices such as whether fish of a particular sex and size cohort were targeted (Royle et al, in review).…”
Section: Prehistoric Trade and Fishing Technologymentioning
confidence: 99%
“…While zooarchaeological analyses are also well-suited to reconstructing catch size profiles, particularly when larger quantities of fish head bones are preserved, there are many cases where this will not be possible using traditional osteological analyses, such as when most fish bones recovered archaeologically are from vertebrae. In these cases, particularly when combined with aDNA techniques (Royle et al, 2018), isotopic analyses of archaeological fish have significant potential to reveal ancient fisheries management practices such as whether fish of a particular sex and size cohort were targeted (Royle et al, in review).…”
Section: Prehistoric Trade and Fishing Technologymentioning
confidence: 99%
“…(n = 1; much larger) based on their size. However, as speciating Pacific salmonid vertebrae through non-biomolecular methods is difficult (See Section Species identification of archaeological Pacific salmonid remains), we used aDNA analysis to confirm species identifications and obtain sex identifications [70,126] for a subset of the archaeological vertebrae (n = 10). Detailed descriptions of the methods employed in the aDNA analysis are provided in the supplementary materials (S2 Text).…”
Section: Ancient Dna Analysismentioning
confidence: 99%
“…DNA was extracted from the decontaminated samples using a silica-spin column method [129] as modified by Yang and colleagues [130]. Sex identities were assigned to the samples using two PCR sex identification assays (termed clock1a/sdY and D-loop/sdY) designed by Royle and colleagues [126]. Following Royle and colleagues [126], we sought to assign species identifications to the remains by sequencing a 249 bp fragment of the mitochondrial D-loop co-amplified as an internal positive control in one of the sex identification assays (D-loop/sdY assay).…”
Section: Ancient Dna Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, multiple studies have reported the successful retrieval of aDNA from archaeological fish bone for a variety of species, locations and age (Oosting et al, 2019). aDNA has been consistently amplified from herring (Speller et al, 2012), Pacific salmon (Grier et al, 2013; Johnson et al, 2018; Royle et al, 2018; Speller et al, 2005; Yang et al, 2004), Atlantic cod (Hutchinson et al, 2015; Ólafsdóttir et al, 2014), sturgeon (Ludwig et al, 2009; Nikulina & Schmölcke, 2016; Pagès et al, 2009), Mediterranean trout (Splendiani et al, 2016), Northern pike (Wooller et al, 2015), and other fish taxa (Arndt et al, 2003; Ciesielski & Makowiecki, 2005; Živaljević et al, 2017), in some cases from bones up to 6,000 yBP or older (Johnson et al, 2018; Nikulina & Schmölcke, 2016; Speller et al, 2012; Splendiani et al, 2016; Wooller et al, 2015; Yang et al, 2004). Fish aDNA has also been successfully amplified in metagenomic analyses using bulk bone approaches, even from warm tropical climates (Grealy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%